Aprendizagem significativa e alinhamento construtivo uma proposta para o ensino de circuitos elétricos - Souza, Pricila Rodrigues de (2016)
The planning and development of teaching practice have significant impact on student learning. This paper explores this impact through a didactic proposal for students of middle level technical courses in electrical circuits teaching. The proposal is structured with nine teaching plans and learning, shared through a series of nine videos, based on Meaningful Learning Theory of David Ausubel and Constructive Alignment teaching model of John Biggs. The strategic action research guided the investigation. For the suitability of the material presented to students in elaborate plans were considered its profile and cognitive structure. To collect research data were made audio recordings of the main stages, logbooks, photographs, experimental activities, interviews, previous conceptual maps and final, as well as the evaluation of the tasks performed at the end of each class. Evidence presented during the application of didactic proposal allow to say that aspects: contextualization of learning, motivation, student monitoring and a new look of the teacher in front of his practice; contribute to the promotion of meaningful learning of students.